SYNTHESIS, CHARACTERIZATION AND EVALUATION OF SURFACTANTS DERIVED FROM NATURAL OILS FOR EOR APPLICATIONS - MUHAMMAD, MUSHTAQ (2012)
Enhanced oil recovery methods are directed towards the recovery of residual oil from a reservoir. Surfactants have been gaining prominence as a main chemical for EOR methods. Natural oils, owing to their naturally long hydrocarbon chains, possess remarkable potential to be used as raw materials for the development of surfactants. The oleic acid methyl esters obtained from Jatropha oil and high oleic acid methyl esters were modified by the attachment of nine different alkoxy groups (derived from alcohols) and these were successfully converted to 18 types of sulfate and sulfonate based anionic surfactants. The high FFA value of Jatropha oil was suppressed to as low as I % by employing an indigenously developed silica based catalyst. The synthesized methyl esters were epoxidized by optimizing the epoxidation process by using the RSM technique utilizing a central composite rotatable design. The DOE successfully optimized the yield and dramatically shortened the reaction time. The obtained oxirane ring was then opened up using nine different alcohols thereby attaching them as alkoxy chains on the oleic acid methyl ester parent chain. Sulfation of the -OH groups located trans to the alkoxy groups yielded nine sulfate type surfactants. For the synthesis of sulfonate surfactants, the -OH group was protected by the acetylation reaction before sulfonation by an S03-air mixture in a falling film reactor, hence producing nine sulfonate based surfactants. The sulfate and sulfonate surfactants were obtained in high yields. All end products and precursors were characterized by GC-FID, GC-MS, FT -IR and NMR techniques.